Cases and materials on the law of the sea - Sohn, Louis B. (Brill Nijhoff, 2014)
This second edition of Cases and Materials on the Law of the Sea compiles cases, treaties, U.N. documents, commentaries, and other teaching materials that systematically present law of the sea topics.